Peran Guru PAI dalam Mengatasi Kesulitan Belajar dengan Menggunakan Model Pembelajaran Contextual Teaching and Learning (CTL) di MTs PINK 03 - ‘Zalsabila, Umrah (Permata : Jurnal Pendidikan Agama Islam, 2024)
This research aims to identify the role of Islamic Religious Education (PAI) teachers in overcoming learning difficulties at MTs. Pink 03 through the application of the Contextual Teaching and Learning (CTL) learning model. This research uses a qualitative method with a descriptive approach. The type of research applied is field research. The data collection techniques used are through observation, interviews and documentation.The results of this research show that PAI teachers effectively utilize the CTL learning model to increase student involvement, understand Islamic concepts, and stimulate interest in learning. The implications of these findings can contribute to the development of more adaptive PAI learning strategies in various educational contexts. Keywords: PAI Teacher; Learning Difficulties; Contextual Teaching and Learning